Hypoxia-Inducible Factor 1-Related Diseases and Prospective Therapeutic Tools - Jong-Wan Park; Yang-Sook Chun; Myung-Suk Kim (Elsevier, 2004)
Hypoxia-inducible factor 1 (HIF-1) is a transcription factor that functions as a master regulator of oxygen homeostasis. HIF-1 regulates the expressions of the proteins that increase oxygen delivery, which enables cells to survive in oxygen-deficient conditions. Based on information as to which types of genes are controlled by HIF-1, it appears that HIF-1 provides pathological tissues with survival in hypoxic regions or angiogenic activity. Therefore, HIF-1 inhibitors could be useful as therapeutic agents for various diseases associated with the over-activation of HIF-1, such as cancers, cardiovascular remodeling, preeclamsia, and other angiogenesis-related diseases. In this review, we summarize the oxygen-dependent and -independent regulation of HIF-1 and introduce prospective HIF-1 inhibitors that might be useful in the treatment of HIF-1-related diseases. Keywords:: hypoxia-inducible factor (HIF), HIF-related disease, HIF competitor, HIF inhibitor